Content analyses of rail companies’ sites and web pages concerning healthy lifestyle promotion and prevention coronavirus infection - Elena A. Zhidkova; Elena A. Okunkova; Konstantin V. Zorin; Konstantin G. Gurevich (Здоровье мегаполиса)
Introduction. The development of modern society implies that more and more information is placed in the digital space. Therefore, the attitude of the management of transport companies to the promotion of healthy lifestyle and the prevention of COVID-19 can be indirectly assessed by the content of their sites and web pages. Purpose. The purpose of this article is a content analysis of rail companies’ sites and web pages on the promotion of healthy lifestyles and the prevention of COVID-19. Materials and methods. The study was carried out once, in October 2020. We analyzed the sites and web pages of rail companies using the formation of queries, as well as using the search engines Yandex and Google. Results. The frequency of mentioning healthy lifestyle issues on the websites and web pages of the analyzed rail companies vary from 32 to 54 %. COVID-19 prevention issues are covered only in a half of cases by railway companies and in more than 90 % – on the websites and web pages of subways, high-speed trams and city trams. In general, the analyzed websites and web pages of the rail companies adequately display the information related to the prevention of COVID. Discussion. Rail companies pay attention to the formation of healthy lifestyles and prevention of COVID-19 on their web pages and sites. For this reason, it can be assumed that the management of the rail companies is concerned about these problems. At the same time, we have no reason to believe that the analyzed web documents fully reflect the ongoing preventive programs, in other words, it can be assumed that the preventive activities of rail companies are broader than shown in this study. Meanwhile, rail companies do not fully cover their social policy regarding the health of their own employees. Conclusion. The sites and web pages of rail companies, as a rule, contain scattered information on promoting healthy lifestyle. At the same time, the information on the prevention of COVID-19 is usually presented in a comprehensive manner. The issues of COVID-19 prevention in general are mentioned on more sites and web pages than the issues of healthy lifestyle formation.